Dynamics of Marital Resilience in Urban Muslim Families: A Couple Therapy Perspective - Hopipah, Eva Nur; Mujib, Abdul; Shaleh, Abdul Rahman (Jurnal Psikologi Islam dan Budaya, 2025)
This research aims to qualitatively explore the dynamics of marital resilience from psychological and theological perspectives through an in-depth literature review, highlighting couple therapy as a conceptual lens to understand and strengthen the relationship between husband and wife. Through an in-depth literature review analyzed using thematic analysis, this study found that Islamic values such as patience (ṣabr), reliance on God (tawakkul), good communication, and collective responsibility significantly contribute to marital resilience. Couple therapy, especially the Acceptance and Commitment Therapy (ACT), Cognitive-Behavioral Therapy (CBT), and Emotion-Focused Therapy (EFT) approaches integrated with Islamic principles, have been shown to be effective in increasing relationship resilience by strengthening emotional and spiritual bonds. These findings confirm that marital resilience does not only depend on individual and relational factors, but also on the integration of deep religious values. Therefore, Islamic-based couple therapy can be a contextual and relevant therapeutic solution.